2020
DOI: 10.3389/fendo.2020.00191
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Its Benefits for Various Diseases

Abstract: Metformin is a widely used biguanide drug due to its safety and low cost. It has been used for over 60 years to treat type 2 diabetes at the early stages because of its outstanding ability to decrease plasma glucose levels. Over time, different uses of metformin were discovered, and the benefits of metformin for various diseases and even aging were verified. These diseases include cancers (e.g., breast cancer, endometrial cancer, bone cancer, colorectal cancer, and melanoma), obesity, liver diseases, cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
218
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(268 citation statements)
references
References 114 publications
4
218
0
3
Order By: Relevance
“…13 This is a particularly important point as studies have shown that metformin can be useful in the treatment of cancers, obesity, liver diseases, renal diseases and cardiovascular diseases which tend to plague older populations. 21 We used results from our study to analyse whether the 1.2% difference in vitamin B 12 deficiency rates between our metformin and comparison populations was significant enough to indicate the need for screening for B 12 deficiency. Using criteria for creating a screening guideline, not all can be met.…”
Section: Discussionmentioning
confidence: 99%
“…13 This is a particularly important point as studies have shown that metformin can be useful in the treatment of cancers, obesity, liver diseases, renal diseases and cardiovascular diseases which tend to plague older populations. 21 We used results from our study to analyse whether the 1.2% difference in vitamin B 12 deficiency rates between our metformin and comparison populations was significant enough to indicate the need for screening for B 12 deficiency. Using criteria for creating a screening guideline, not all can be met.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the adipose tissue mass and increases the tissue sensitivity to insulin, thereby reducing hyperglycemia, normalizing carbohydrate and lipid metabolism and preventing inflammation and oxidative stress in the tissues [ 1 , 2 ]. MF is also used to treat non-alcoholic fatty liver disease [ 3 ], coronary artery disease [ 4 , 5 ], acute kidney injury and chronic kidney disease [ 6 ], in patients with T2DM, metabolic syndrome (MetS) and obesity, and in patients without apparent symptoms of metabolic disorders [ 7 ]. There are numerous clinical and experimental studies indicating the effectiveness of MF as an anticancer drug, used to prevent the growth and metastasis in breast cancer [ 8 , 9 ], endometrial cancer [ 10 , 11 , 12 ], colorectal cancer [ 9 , 13 ], prostate cancer [ 14 ] and in a number of the other tumors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on interventions aimed at reducing IR may offer a benefit such as the reduction of the risk of CVD in patients with T1DM. According to Lv & Guo [ 29 ]; Metformin has an array of other benefits. Fig.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%